Fermentation improves antioxidant capacity and γ-aminobutyric acid content of Ganmai Dazao Decoction by lactic acid bacteria - Wei, Linya; Li, Yiming; Hao, Zina; Zheng, Zhenjie; Yang, Huixin; Xu, Suixin; Li, Shihan; Zhang, Lili; Xu, Yunhe (Frontiers in Microbiology, 2023)
Introduction: Ganmai Dazao Decoction is a traditional Chinese recipe, and is composed of licorice, floating wheat, and jujube. Methods: Effects of lactic acid bacteria fermentation on the physicochemical properties, antioxidant activity, and γ-aminobutyric acid of Ganmai Dazao Decoction were studied. The changes of small and medium molecules in Ganmai Dazao Decoction before and after fermentation were determined by LC-MS non-targeted metabolomics. Results: The results showed that the contents of lactic acid, citric acid, acetic acid and total phenol content increased significantly, DPPH free radical clearance and hydroxyl free radical clearance were significantly increased. γ-aminobutyric acid content was 12.06% higher after fermentation than before fermentation. A total of 553 differential metabolites were detected and identified from the Ganmai Dazao Decoction before and after fermentation by partial least squares discrimination and VIP analysis. Discussion: Among the top 30 differential metabolites with VIP values, the content of five functional substances increased significantly. Our results showed that lactic acid bacteria fermentation of Ganmai Dazao Decoction improve its antioxidant effects and that fermentation of Ganmai Dazao Decoction with lactic acid bacteria is an innovative approach that improves the health-promoting ingredients of Ganmai Dazao Decoction.